Economical evaluation of logistics centres establishment - Meidutė, Ieva (Transport, 2007)
This paper presents a method for assessing the financial viability of a new Freight village financed by private and public investments. The financial evaluation model constitutes four distinct phases, namely (a) site selection and traffic forecasts, (b) definition of services offered and corresponding dimensions, (c) estimation of investment and operation costs and (d) evaluation of investments. Furthermore, the model produces financing scenarios, based on combinations of public and private funds.First Published Online: 27 Oct 2010